Antecedents to Revenge Tourism with an Expanded Theory of Planned Behavior in Jabodetabek Region - Endra Dewi, Yuliana; Sutanto, Tommy Wijaya; Permana, Febry Indra; Hendriana, Evelyn (Journal of Indonesian Tourism and Development Studies, 2023)
Revenge tourism is a manifestation of tourist expressions to make up for lost time due to the pandemic. This study aims to explore the factors that encourage someone to engage in revenge tourism by using an expanded Theory of Planned Behavior (TPB). The population in this study were Jabodetabek residents in adulthood who had traveled during the easing of restrictions. Sampling using convenience sampling technique with a total sample of 246 people. This study used a quantitative approach, and data were collected through questionnaires distributed online using Google Forms. The data analysis technique in this study uses Partial Least Square (PLS). PLS is an equation model of Structural Equation Modeling (SEM) with an approach based on variance or component-based structural equation modeling. The results of this study provide insight into the factors that influence a person's intention to engage in revenge tourism and can be used to develop effective policies and marketing strategies in tourism. Keywords: Covid-19, PPKM, perceived risk, planned behavior, revenge tourism, travel stimulus.